2017
DOI: 10.3390/jmse5040046
|View full text |Cite
|
Sign up to set email alerts
|

SISI: A New Device for In Situ Incubations at the Ocean Surface

Abstract: Abstract:The sea-surface microlayer (SML) forms the uppermost boundary layer between atmosphere and ocean, and has distinctive physico-chemical and biological features compared to the underlying water. First findings on metabolic contributions of microorganisms to gas exchange processes across the SML raised the need for new in situ technologies to explore plankton-oxygen turnover in this special habitat. Here, we describe an inexpensive research tool, the Surface In Situ Incubator (SISI), which allows simulta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 50 publications
0
10
0
Order By: Relevance
“…NCP rates in the SML were generally higher compared to ULW (Figure 4 and Supplementary Figure 4), and enhanced metabolic activity, especially of heterotrophic bacteria, is a well-known feature of the SML (Obernosterer et al, 2005;Reinthaler et al, 2008). Other studies reported SML NCP rates between −0.4 to +1.0 µmol O 2 L −1 h −1 for different coastal marine systems (Obernosterer et al, 2005;Rahlff et al, 2017b). The NCP rates in the SML of the present study (−21.3 to 44.8 µmol O 2 L −1 h −1 ) are several 10-folds higher, which was most likely caused by the large number of auto-and heterotrophic microorganisms.…”
Section: Neuston Activity In Thick Surface Filmsmentioning
confidence: 84%
See 1 more Smart Citation
“…NCP rates in the SML were generally higher compared to ULW (Figure 4 and Supplementary Figure 4), and enhanced metabolic activity, especially of heterotrophic bacteria, is a well-known feature of the SML (Obernosterer et al, 2005;Reinthaler et al, 2008). Other studies reported SML NCP rates between −0.4 to +1.0 µmol O 2 L −1 h −1 for different coastal marine systems (Obernosterer et al, 2005;Rahlff et al, 2017b). The NCP rates in the SML of the present study (−21.3 to 44.8 µmol O 2 L −1 h −1 ) are several 10-folds higher, which was most likely caused by the large number of auto-and heterotrophic microorganisms.…”
Section: Neuston Activity In Thick Surface Filmsmentioning
confidence: 84%
“…As described above, the 0 µm water depth was defined by the intersecting linear regression lines of air and water temperature readings. To account for minor vertical changes of the water temperature in the tank within the upper centimeters ( Supplementary Figure 3), the O 2 profile data was temperature-corrected for each individual depth according to Rahlff et al (2017b) and Unisense supportive material.…”
Section: Temperature-correction Of O 2 Gradientsmentioning
confidence: 99%
“…The probability of viral infection and lysis of prokaryotes has been shown to increase within the SML due to the higher density of both viruses and hosts [ 8 ]. This would promote the leaching of dissolved organic matter from lysed cells, favoring the growth of other heterotrophic microorganisms [ 11 , 12 ]. However, it has been reported that extreme environmental conditions may affect the viral life strategy [ 13 ] and the physiological state of hosts [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Life at air–water interfaces has never been considered easy, mainly because of the harsh environmental conditions that influence the SML [ 11 ]. However, high abundances of microorganisms, especially of bacteria and picophytoplankton, accumulating in the SML compared to the underlying water were frequently reported [ 4 , 12 , 13 ], accompanied by a predominant heterotrophic activity [ 14 , 15 , 16 ]. This is because primary production at the immediate air–water interface is often hindered by photoinhibition [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%